2017
DOI: 10.1155/2017/5769837
|View full text |Cite
|
Sign up to set email alerts
|

More Than a Decade of Misdiagnosis of Alternating Hemiplegia of Childhood with Catastrophic Outcome

Abstract: Alternating hemiplegia of childhood (AHC) is a distinct clinical disorder characterized by recurrent episodes of hemiplegia, abnormal ocular movement, and progressive developmental delay. It is an extremely rare genetic disorder related to ATP1A3 gene mutations. In this paper, we present a case of AHC in which the diagnosis was missed for many years until severe hypoxic brain insult occurred from prolonged status epilepticus. Not only we are presenting an interesting clinical entity and radiological images, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…It is important to educate the Saudi population about this fact to hopefully reduce the occurrence of rare and devastating diseases. We have previously reported several novel and rare mutations causing a wide variety of genetic neurological diseases in the Saudi community (16)(17)(18)(19)(20)(21)(22)(23)(24). This paper may be considered as an urgent call for action to address the consanguinity issue in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 91%
“…It is important to educate the Saudi population about this fact to hopefully reduce the occurrence of rare and devastating diseases. We have previously reported several novel and rare mutations causing a wide variety of genetic neurological diseases in the Saudi community (16)(17)(18)(19)(20)(21)(22)(23)(24). This paper may be considered as an urgent call for action to address the consanguinity issue in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 91%
“…Premarital or preimplantation genetic screening allows a genetic diagnosis early on and can help couples who carry the same disease-causing variants to make an informed decision regarding their marriage and the consequences of their decision. The current authors have previously reported a wide variety of novel and rare genetic mutations causing a broad spectrum of diseases and clinical manifestations in the Saudi community (17)(18)(19)(20)(21)(22)(23)(24). Molecular testing of potential carriers of those mutations may be urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…In association with hemiplegic episodes, tonic and dystonic movements, choreoathetosis, ataxia, nystagmus, and oculomotor abnormalities are often observed. [1,2,[5][6][7][8] One of the largest AHC studies was conducted by Sweney et al [4] who reported 103 individuals (56 females and 47 males). According to these authors, [4] the most frequent and early symptoms observed in the first 3 months of life were paroxysmal eye movements in 83% and hemiplegic episodes by 6 months in 56% of patients.…”
Section: Symptoms and Signsmentioning
confidence: 99%
“…Recent diagnostic criteria were dictated by Rosewich et al [18] and Mikaki et al [24] who found that most AHC individuals show a variable degree of associated disorders such as neuropsychological abnormalities, DD/ID, epileptic seizures, motor dysfunction, abnormal movements, migraine, sleep, and cardiac disturbances. [5][6][7][8] 3.3. Clinical manifestations besides the hemiplegic events 3.3.1.…”
Section: Symptoms and Signsmentioning
confidence: 99%